The Turkish rule and the strategies of its description in the Old Serbian literature (following the example of the brief literary forms – notations - Lis-Wielgosz, Izabela (Balcanica Posnaniensia. Acta et studia, 2014)
In the article, a problem of conceiving and depicting the Turkish rule is taken into account, for my reflections concentrate on the patterns of presentation regarding the Ottoman Turks’ invasion of the Balkan territory, and their oppressive rule in the Balkans. The patterns mentioned above, present in the Old Serbian literature, were to commemorate all those tragic events. In the Old Serbian texts (pertaining to hagiography, historiography, hymnic literature, and also to the brief literary forms – notations), the Turkish rule was expressed in explicitly negative categories of illegality, violence, and godlessness, presented in the context of the “end of times”, the Christian community’s martyrdom, mentioned in the eschatological perspective of the definition of history and exegesis, the perspective so characteristic for the Middle Ages.